Rice straw derived cellulose acetate / g-C3N4 / TiO2 fiber membrane as well as preparation method and application thereof

Through electrospinning-electrospraying technology, the g-C3N4/TiO2 nanocomposite material is anchored on cellulose acetate nanofibers, which solves the problem of poor photocatalytic effect caused by poor nanoparticle distribution in the prior art, and achieves the efficient photocatalytic degradation effect under visible light.

CN119593143APending Publication Date: 2025-03-11WUHAN POLYTECHNIC UNIVERSITY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411617957.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

In the prior art, the inherent energy band and band gap width of TiO2 and g-C3N4 limit their photocatalytic applications under visible light, and the distribution of nanoparticles within the fiber leads to poor photocatalytic effects.

Method used

Through electrospinning-electrospraying technology, the g-C3N4/TiO2 nanocomposite is anchored on cellulose acetate nanofibers to ensure that the nanoparticles are uniformly exposed to the fiber surface and improve photocatalytic performance.

Benefits of technology

It realizes efficient degradation of organic pollutants and pathogenic microorganisms in water under visible light, improves photocatalytic performance and material circulation performance, and has a low process cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119593143A_ABST
    Figure CN119593143A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of crop straw recycling, and discloses a rice straw derived cellulose acetate / g-C3N4 / TiO2 fiber membrane as well as a preparation method and application thereof. The preparation method comprises the following steps: uniformly mixing dichloromethane and acetic acid to obtain a mixed solvent, adding rice straw derived cellulose acetate (CA) and polyvinylpyrrolidone (PVP) powder into the mixed solvent, and stirring to obtain a CA / PVP spinning solution; the preparation method comprises the following steps: heating urea to obtain g-C3N4 nanosheets, and freezing and grinding the g-C3N4 nanosheets and TiO2 powder to obtain g-C3N4 / TiO2 powder; the g-C3N4 / TiO2 powder is placed in an absolute ethyl alcohol solution to be stirred, and a g-C3N4 / TiO2 powder electronic injection solution is obtained; according to the electrostatic spinning-electronic injection technology (Electrospinning-electronic injection), a CA / PVP spinning solution and a g-C3N4 / TiO2 powder electronic injection solution are used for conducting electrostatic spinning and electrostatic spraying at the same time, an EE-CA / PVP / g-C3N4 / TiO2 fiber membrane is obtained, then the EE-CA / PVP / g-C3N4 / TiO2 fiber membrane is soaked in deionized water, freeze drying is conducted, and the rice straw derived cellulose acetate / g-C3N4 / TiO2 fiber membrane is obtained. The rice straw derived cellulose acetate / g-C3N4 / TiO2 fiber membrane has excellent photocatalytic performance, and can be widely applied to the fields of degradation of pollutants in water and sterilization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of crop straw resource utilization, and in particular to a rice straw-derived cellulose acetate / g-C3N4 / TiO2 fiber membrane and a preparation method and application thereof. Background Art

[0002] Semiconductor photocatalysis technology is considered to be a favorable technology to solve the global energy shortage and environmental pollution problems. TiO2 has the advantages of non-toxicity, low cost, high oxidation ability, excellent photochemical stability, good chemical inertness and environmental friendliness. g-C3N4 is a photocatalyst that is sensitive to visible light and durable. It has many advantages such as non-toxicity, thermal stability, good chemical inertness, easy synthesis, and moderate energy band gap. These two semiconductors have attracted widespread attention in the field of sunlight-driven photocatalysis due to their significant advantages. However, the huge inherent energy band energy of TiO2 (3.2eV for anatase phase and 3.0eV for rutile phase) and wide bandgap width can only be used under ultraviolet light. Similarly, g-C3N4 also has disadvantages such as low specific surface area, small number of active sites and limited charge mobility, which also limits the practical application of g-C3N4 in the field of photocatalysis.

[0003] In addition, rice straw is a lignocellulosic biomass and an annually renewable agricultural waste, with the main chemical components of cellulose, hemicellulose, lignin and ash. At present, the utilization efficiency of agricultural waste is not high, such as incineration, landfill composting and livestock feed. Cellulose in rice straw can be used as a raw material for the production of cellulose acetate (CA), which is another way to reduce environmental pollution. By loading g-C3N4 / TiO2 nanocomposites on a fiber matrix to prepare nanofiber materials, it can not only promote charge carrier separation and improve light absorption in the visible light region, thereby efficiently degrading organic pollutants and pathogenic microorganisms in water, effectively alleviating energy shortages and solving environmental pollution problems, but also recycle and effectively utilize agricultural waste, reduce environmental pollution, and achieve efficient utilization of rice straw resources.

[0004] In the prior art, the preparation of the loaded fiber membrane generally involves blending cellulose acetate (CA) with nanoparticles, the particles are mainly located inside the fiber, and only when the amount of titanium dioxide and carbon nitride added is very large will the particles be exposed outside the fiber to play a photocatalytic role, and the internal particles cannot play a photocatalytic role, resulting in poor overall photocatalytic effect of the loaded fiber membrane. Therefore, the present application uses electrospinning-electrospray technology, that is, electrospinning and electrostatic spraying are performed simultaneously, to anchor the g-C3N4 / TiO2 nanocomposite material on cellulose acetate (CA) nanofibers, efficiently degrade organic pollutants and pathogenic microorganisms in water, effectively alleviate energy shortages and solve environmental pollution problems, and at the same time realize the high-value utilization of rice straw resources. Summary of the invention

[0005] Based on the above, the purpose of the present invention is to provide a rice straw-derived cellulose acetate / g-C3N4 / TiO2 fiber membrane and a preparation method and application thereof, so as to prepare an environmentally friendly cellulose membrane catalyst with excellent photocatalytic performance, good recycling performance and easy recovery.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] A method for preparing a rice straw-derived cellulose acetate / g-C3N4 / TiO2 fiber membrane comprises the following steps:

[0008] Mixing dichloromethane and acetic acid uniformly to obtain a mixed solvent, adding rice straw-derived cellulose acetate and polyvinyl pyrrolidone powder into the mixed solvent and stirring to obtain a CA / PVP spinning solution;

[0009] The urea is heated in a muffle furnace to prepare g-C3N4 nanosheets, the g-C3N4 nanosheets and TiO2 powder are weighed and put into a cryogenic grinding machine, and the cryogenic grinding parameters are adjusted to grind to obtain g-C3N4 / TiO2 powder;

[0010] The g-C3N4 / TiO2 powder is placed in an anhydrous ethanol solution, subjected to ultrasonic treatment, and subjected to magnetic stirring to obtain a g-C3N4 / TiO2 powder electrospray solution;

[0011] EE-CA / PVP / g-C3N4 / TiO2 fiber membrane was prepared by electrospinning-electrospray technology, CA / PVP spinning solution and g-C3N4 / TiO2 powder electrospray solution were used for electrospinning and electrospinning respectively, g-C3N4 / TiO2 powder was evenly anchored on the fiber surface, and EE-CA / PVP / g-C3N4 / TiO2 fiber membrane was obtained;

[0012] The EE-CA / PVP / g-C3N4 / TiO2 fiber membrane was immersed in deionized water to remove polyvinyl pyrrolidone, and then freeze-dried to obtain a rice straw-derived cellulose acetate / g-C3N4 / TiO2 fiber membrane.

[0013] As a preferred embodiment of the method for preparing a rice straw-derived cellulose acetate / g-C3N4 / TiO2 fiber membrane, the mass ratio of the rice straw-derived cellulose acetate and the polyvinyl pyrrolidone powder is (3-5):1; the volume ratio of the dichloromethane and the acetic acid is (1-3):1, and the concentration of the polyvinyl pyrrolidone powder in the mixed solvent is 0.025-0.05 g / mL.

[0014] As a preferred embodiment of the method for preparing a rice straw-derived cellulose acetate / g-C3N4 / TiO2 fiber membrane, the concentration of the g-C3N4 / TiO2 powder relative to the mixed solvent is 0.01 to 0.025 g / mL; in the g-C3N4 / TiO2 powder electrospray solution, the concentration of the g-C3N4 / TiO2 powder relative to the anhydrous ethanol is 0.003 to 0.01 g / mL.

[0015] As a preferred scheme for the preparation method of rice straw-derived cellulose acetate / g-C3N4 / TiO2 fiber membrane, when heating the reaction in the muffle furnace, the temperature is raised to 500-550°C at a rate of 3-6°C / min and kept warm for 4-6 hours; when the g-C3N4 nanosheets and the TiO2 powder are ground, the mass ratio is 1:1; the frozen grinding parameters include: grinding time of 30-90s, and grinding frequency of 25-35Hz.

[0016] As a preferred embodiment of the preparation method of rice straw-derived cellulose acetate / g-C3N4 / TiO2 fiber membrane, the electrospinning-electrospray technology device comprises an electrospinning machine, an electrostatic sprayer and a rotary drum collecting device, wherein the electrospinning machine is placed on one side of the rotary drum collecting device, and the electrostatic sprayer is placed on the other side of the rotary drum collecting device; when the electrospinning-electrospray technology is performed, the electrospinning machine and the electrostatic sprayer are used simultaneously to perform electrospinning and electrostatic spraying respectively, and a rotary drum collecting device is used for collection, wherein the electrostatic sprayer is not connected to a high-voltage power supply when in use, and the electrospinning-electrospray technology allows the nanoparticles in the electrospray liquid to be evenly dispersed on the fiber surface.

[0017] As a preferred scheme for the preparation method of rice straw-derived cellulose acetate / g-C3N4 / TiO2 fiber membrane, the electrospinning process parameters include: spinning temperature of 23-27°C, humidity of 45-55%; spinning positive voltage of 8-12kV, spinning negative voltage of -4--6kV; feed rate of 0.3-0.5ul / min; the distance between the spinneret and the drum collecting device is 10-20cm.

[0018] As a preferred embodiment of a method for preparing a rice straw-derived cellulose acetate / g-C3N4 / TiO2 fiber membrane, the method for preparing the rice straw-derived cellulose acetate comprises:

[0019] The rice straw is washed, dried, crushed and sieved to obtain rice straw powder, the rice straw powder is pretreated with an ethanol solution in a high temperature reactor, and then subjected to an alkali treatment and H2O2 bleaching to obtain rice straw-derived cellulose;

[0020] Acetic anhydride and glacial acetic acid are added to the rice straw-derived cellulose to prepare rice straw-derived cellulose acetate through acetylation reaction.

[0021] As a preferred embodiment of the method for preparing a rice straw-derived cellulose acetate / g-C3N4 / TiO2 fiber membrane, the rice straw particle size is 50-100 meshes;

[0022] During the pretreatment process, the mass concentration of the ethanol solution is 60-70wt%, the heating reaction temperature is 160-240°C, and the reaction time is 2-3h;

[0023] During the alkali treatment and H2O2 bleaching process, 4-6 wt% alkali solution is used to stir and react at 85-95°C for 1.5-2.5 hours, and after the reaction is completed, it is filtered, and then heated and stirred with 2 wt% H2O2 solution at 65-75°C for 1.5-2.5 hours to obtain rice straw-derived cellulose;

[0024] During the acetylation reaction, the mass ratio of the rice straw-derived cellulose to the acetic anhydride is 1:(3-5), and the concentration range of the rice straw-derived cellulose in the glacial acetic acid is 0.05-0.07 g / mL.

[0025] A rice straw-derived cellulose acetate / g-C3N4 / TiO2 fiber membrane is prepared by any of the preparation methods described above.

[0026] The invention discloses an application of a rice straw-derived cellulose acetate / g-C3N4 / TiO2 fiber membrane. The rice straw-derived cellulose acetate / g-C3N4 / TiO2 fiber membrane is used as a photocatalyst in water pollution treatment and photocatalytic sterilization.

[0027] The beneficial effects of the present invention are:

[0028] The present invention provides a rice straw derived cellulose acetate / g-C3N4 / TiO2 fiber membrane and a preparation method and application thereof, wherein a freezing grinding technique is used to tightly combine g-C3N4 / and TiO2, and a g-C3N4 / TiO2 catalyst (CG-CN / P25) is prepared, and the catalyst is loaded onto a nanofiber by an electrospinning-electrospray technique to prepare an EE-CA / CGCN / P25 fiber membrane, and compared with a conventional electrospinning method, the g-C3N4 / TiO2 particles of the EE-CA / CGCN / P25 fiber membrane are more exposed on the surface of the nanofiber, providing more active sites, which is beneficial to improving the photocatalytic performance. At the same time, the EE-CA / CGCN / P25 fiber membrane exhibits a lower band gap, a larger specific surface area, and a stronger superhydrophilicity. In addition, the present application uses an electrostatic sprayer for electrostatic spraying, and the electrostatic sprayer does not need to be connected to a high voltage power supply when used, is easy to use, and reduces process costs.

[0029] The EE-CA / CGCN / P25 fiber membrane was used for photocatalytic degradation of RhB. The results showed that the catalyst could achieve a RhB degradation rate of more than 99% when the light was irradiated for 8 minutes. In addition, when the CG-CN / P25 loading was 0.10 g, the EE-CA / CGCN / P25 (0.10) The fiber membrane exhibited the best photocatalytic activity, with a degradation rate of more than 99.80% for MB and more than 92.10% for TC in 30 minutes, and showed good stability and reusability after multiple cycles. It has excellent degradation performance for RhB, MB, and TC, and can efficiently degrade pollutants.

[0030] Evaluation of EE-CA / CGCN / P25 by photocatalytic antibacterial test (0.10) The antibacterial properties of the fiber membrane. The test results show that when irradiated with λ>420nm light for 60min, EE-CA / CGCN / P25 (0.10) The antibacterial rate against Escherichia coli reached more than 99.90%. (0.10) Fiber membrane catalysts have broad application prospects in the fields of degradation of water pollutants and antibacterial properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments of the present invention. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the contents of the embodiments of the present invention and these drawings without paying any creative work.

[0032] Figure 1 The degradation curve of rhodamine B: (a) different grinding ball diameters; (b) different grinding time; (c) different grinding frequency; (d) different ratios of g-C3N4 and P25;

[0033] Figure 2 SEM images and HR-TEM images, among which (ab) SEM images of CG-CN / P25; (cd) EE-CA / CGCN / P25 (0.05) SEM images of EE-CA / CGCN / P25; (ef) (0.10) SEM image of (gh)EE-CA / CGCN / P25 (0.15) SEM images of E-CA / CGCN / P25; (ij) (0.10) SEM images of EE-CA / CGCN / P25; (ij) (0.10) HR-TEM image of fiber membrane;

[0034] Figure 3 CN / P25, CG-CN / P25, E-CA / CGCN / P25 (0.10) and XRD spectra of EE-CA / CGCN / P25 fiber membranes with different CG-CN / P25 contents;

[0035] Figure 4 CN / P25, CG-CN / P25, E-CA / CGCN / P25 (0.10) and FT-IR spectra of EE-CA / CGCN / P25 fiber membranes with different CG-CN / P25 contents;

[0036] Figure 5 These are the EDS and Mapping diagrams of CG-CN / P25, where (a) EDS diagram of CG-CN / P25; (b) Mapping diagram of CG-CN / P25; (c) Mapping diagram of C element; (d) Mapping diagram of N element; (e) Mapping diagram of O element; (f) Mapping diagram of Ti element;

[0037] Figure 6 EE-CA / CGCN / P25 (0.10) EDS and mapping images of fiber membranes, where (a) EE-CA / CGCN / P25 (0.10) EDS image of fiber membrane; (b) EE-CA / CGCN / P25 (0.10) Mapping diagram of (c) C element; (d) N element; (e) O element; (f) Ti element;

[0038] Figure 7 CN / P25, CG-CN / P25, EE-CA / CN / P25 (0.10) and E-CA / CN / P25 (0.10) N2 adsorption-desorption isotherms and pore size distribution of fiber membrane;

[0039] Figure 8 is the UV-visible diffuse reflectance spectrum and energy band curve diagram, where (a) EE-CA / CGCN / P25 and E-CA / CGCN / P25 with different CG-CN / P25 contents (0.10) UV-visible diffuse reflectance spectrum of fiber membrane; (b) EE-CA / CGCN / P25 (0.10) and E-CA / CGCN / P25 (0.10) Energy band diagram of fiber membrane;

[0040] Fig. 9CN / P25, CG-CN / P25, EE-CA / CGCN / P25 fiber membranes with different CG-CN / P25 contents, and E-CA / CGCN / P25 (0.10) Fluorescence spectrum of fiber membrane;

[0041] Fig.10 It curve and EIS spectrum, where (a) EE-CA / CGCN / P25 (0.10) and E-CA / CGCN / P25 (0.10) Fiber membrane it curve; (b) EIS spectrum;

[0042] Fig.11 CA, EE-CA / CGCN / P25 (0.10) and E-CA / CGCN / P25 (0.10) The test results of the contact angle of the fiber membrane to water;

[0043] Fig.12 is the photocatalytic degradation efficiency and the corresponding pseudo-first-order rate constant, where (ab) the photocatalytic degradation efficiency of methylene blue and the corresponding pseudo-first-order rate constant; (cd) the photocatalytic degradation efficiency of tetracycline and the corresponding pseudo-first-order rate constant; (ef) EE-CA / CGCN / P25 (0.10) Degradation efficiency of fiber membranes for different dyes and the corresponding pseudo-first-order rate constants;

[0044] Fig.13 EE-CA / CGCN / P25 (0.10) Repeated test diagram of the fiber membrane's photocatalytic degradation of methylene blue;

[0045] Fig.14 EE-CA / CGCN / P25 (0.10) Time-varying diagram of the 3D fluorescence spectrum of the fiber membrane, where (ac) methylene blue; (df) rhodamine B; (gi) methyl orange;

[0046] Fig.15 EE-CA / CGCN / P25 (0.10) Degradation efficiency of methylene blue by fiber membrane under the action of different quenchers (a) and the corresponding pseudo-first-order rate (b);

[0047] Fig.16 The antibacterial effect images, bacterial survival rate curves and bacterial removal efficiency bar graphs, where (ad) blank test; (eh) EE-CA / CGCN / P25 (0.10) Dark's antibacterial effect image; (il)EE-CA / CGCN / P25 (0.10)Image of Lighton’s antibacterial effect; (m) bacterial survival rate curve; (n) histogram of bacteria removal efficiency of samples under visible light (λ>420nm). DETAILED DESCRIPTION

[0048] For ease of understanding of the present invention, the present invention will be described more fully below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive. Unless otherwise defined, all technical and scientific terms used in the present invention belong to the technical field of the present invention.

[0049] This embodiment provides a method for preparing a rice straw-derived cellulose acetate / g-C3N4 / TiO2 fiber membrane, comprising the following steps:

[0050] S100, mixing dichloromethane and acetic acid uniformly to obtain a mixed solvent, adding rice straw-derived cellulose acetate and polyvinyl pyrrolidone powder into the mixed solvent and stirring to obtain a CA / PVP spinning solution;

[0051] Specifically, the mass ratio of rice straw-derived cellulose acetate and polyvinyl pyrrolidone powder is (3-5):1; the volume ratio of dichloromethane and acetic acid is (1-3):1, and the concentration of polyvinyl pyrrolidone powder in the mixed solvent is 0.025-0.05 g / ml.

[0052] S200, heating urea in a muffle furnace to prepare g-C3N4 nanosheets, weighing the g-C3N4 nanosheets and TiO2 powder, putting them into a cryogenic grinding machine, adjusting the cryogenic grinding parameters, and grinding to obtain g-C3N4 / TiO2 powder;

[0053] Specifically, when heating the reaction in the muffle furnace, the temperature is raised to 500-550°C at a rate of 3-6°C / min and kept warm for 4-6 hours. When the g-C3N4 nanosheets and TiO2 powder are ground, the mass ratio is 1:1; the freezing grinding parameters include: the grinding time is 30-90s, and the grinding frequency is 25-35Hz.

[0054] S300, placing g-C3N4 / TiO2 powder in anhydrous ethanol solution, ultrasonically treating, and magnetically stirring to obtain a g-C3N4 / TiO2 powder electrospray solution;

[0055] Specifically, the concentration of g-C3N4 / TiO2 powder relative to the mixed solvent is 0.01-0.025 g / mL, and the concentration of g-C3N4 / TiO2 powder relative to anhydrous ethanol is 0.003-0.01 g / mL. Exemplarily, 0.8 g of rice straw-derived cellulose acetate, 0.2 g of polyvinyl pyrrolidone powder, and a mixed solvent including 2 ml of acetic acid and 4 ml of dichloromethane are used. At this time, 0.05-0.15 g of g-C3N4 / TiO2 powder is reacted with 15 ml of anhydrous ethanol solution to prepare a g-C3N4 / TiO2 powder electrospray solution for electrospray loading, preferably 0.10 g of g-C3N4 / TiO2 powder is reacted with 15 ml of anhydrous ethanol solution.

[0056] S400, preparing EE-CA / PVP / g-C3N4 / TiO2 fiber membrane by electrospinning-electrospray technology, using CA / PVP spinning solution and g-C3N4 / TiO2 powder electrospray solution to simultaneously perform electrospinning and electrospinning, respectively, and evenly anchoring g-C3N4 / TiO2 powder on the fiber surface to obtain EE-CA / PVP / g-C3N4 / TiO2 fiber membrane;

[0057] Specifically, the g-C3N4 / TiO2 powder is loaded on the cellulose acetate nanofibers using the electrospinning-electrospinning technology. Pure cellulose acetate fibers are obtained by electrospinning while nanoparticles containing g-C3N4 / TiO2 powder are electrosprayed. While the fibers are solidified, the g-C3N4 / TiO2 particles are directly exposed on the fiber surface. There are no nanoparticles inside the fibers, exposing more active sites, hindering the recombination of free carriers, and improving the separation efficiency of photogenerated carriers and the interfacial charge transfer efficiency, thereby improving the catalytic activity and chemical stability of the material.

[0058] Specifically, the device of electrostatic spinning-electrospray technology includes an electrostatic spinning machine, an electrostatic sprayer and a rotary drum collection device, the electrostatic spinning machine is placed on one side of the rotary drum collection device, and the electrostatic sprayer is placed on the other side of the rotary drum collection device; when performing electrostatic spinning-electrospray technology, the electrostatic spinning machine and the electrostatic sprayer are used simultaneously to perform electrostatic spinning and electrostatic spraying respectively, and the rotary drum collection device is used for collection. Preferably, the positions of the electrostatic spinning machine, the electrostatic sprayer and the rotary drum collection device can be in a straight line. Of course, in other embodiments, the positions of the electrostatic spinning machine, the electrostatic sprayer and the rotary drum collection device can also be placed at an angle, and the spray generated by the electrostatic sprayer can be loaded onto the fiber filaments collected by the collection device. In addition, an electrostatic sprayer is used for electrostatic spraying. The electrostatic sprayer does not need to be connected to a high-voltage power supply when used, is easy to use, and reduces process costs. In this embodiment, it is preferably a handheld electrosprayer, which is convenient to operate and reduces process costs. Of course, in other embodiments, a fixed electrosprayer can also be used to meet the load.

[0059] More specifically, the process parameters of electrospinning include: spinning temperature of 23-27°C, humidity of 45-55%; spinning positive voltage of 8-12kV, spinning negative voltage of -4--6kV; feed rate of 0.3-0.5ul / min; the distance between the spinneret and the drum collection device is 10-20cm.

[0060] S500. Soak the EE-CA / PVP / g-C3N4 / TiO2 fiber membrane in deionized water to remove polyvinyl pyrrolidone, and freeze-dry it to obtain a rice straw-derived cellulose acetate / g-C3N4 / TiO2 fiber membrane, which is recorded as EE-CA / CGCN / P25 fiber membrane.

[0061] Specifically, the preparation method of rice straw-derived cellulose acetate includes:

[0062] S001, washing, drying, crushing and sieving the rice straw to obtain rice straw powder, pre-treating the rice straw powder with an ethanol solution in a high-temperature reactor, and then performing an alkali treatment and H2O2 bleaching to obtain rice straw-derived cellulose;

[0063] The rice straw particle size is 50-100 mesh;

[0064] During the pretreatment process, the mass concentration of the ethanol solution is 60-70wt%, the heating reaction temperature is 160-240°C, and the reaction time is 2-3h;

[0065] During the alkali treatment and H2O2 bleaching process, 4-6 wt% alkali solution is stirred at 85-95°C for 1.5-2.5 hours, filtered after the reaction is completed, and then heated and stirred at 65-75°C for 1.5-2.5 hours with 2 wt% H2O2 solution to obtain rice straw-derived cellulose;

[0066] S002, adding acetic anhydride and glacial acetic acid to rice straw-derived cellulose to prepare rice straw-derived cellulose acetate through acetylation reaction;

[0067] The mass ratio of rice straw-derived cellulose to acetic anhydride is 1:(3-5), and the concentration range of rice straw-derived cellulose in glacial acetic acid is 0.05-0.07 g / mL. In a specific embodiment, 7-9 mL of glacial acetic acid is added to every 0.5 g of rice straw cellulose for reaction.

[0068] The present invention will be further described below by means of specific examples.

[0069] Example 1

[0070] The rice straw is washed, dried, crushed and sieved to obtain rice straw powder, and the rice straw powder is pretreated with an ethanol solution in a high-temperature reactor at 200° C. for 3 h, and then subjected to alkali treatment and H2O2 bleaching to obtain rice straw-derived cellulose; 2 g of acetic anhydride and 8 ml of glacial acetic acid are added to 0.5 g of rice straw-derived cellulose to obtain rice straw-derived cellulose acetate through an acetylation reaction; of course, in other embodiments, 1.5 g of acetic anhydride and 7 ml of glacial acetic acid are added to 0.5 g of rice straw-derived cellulose, or 2.5 g of acetic anhydride and 9 ml of glacial acetic acid are added to 0.5 g of rice straw-derived cellulose to obtain rice straw-derived cellulose acetate through an acetylation reaction, which is determined according to actual conditions.

[0071] 4 ml of dichloromethane and 2 ml of acetic acid were evenly mixed to obtain a mixed solvent, 0.8 g of rice straw-derived cellulose acetate and 0.2 g of polyvinyl pyrrolidone powder were added to the mixed solvent, and stirred for 6 hours using a magnetic stirrer to obtain a CA / PVP spinning solution; at this time, the mass ratio of rice straw-derived cellulose acetate and polyvinyl pyrrolidone powder was 4:1; the volume ratio of dichloromethane and acetic acid was 2:1, and the concentration of polyvinyl pyrrolidone powder in the mixed solvent was 0.033 g / mL. Of course, in other embodiments, the mass ratio of rice straw-derived cellulose acetate and polyvinyl pyrrolidone powder was 3:1 or 5:1; the volume ratio of dichloromethane and acetic acid was 3:1 or 1:1, and the concentration of polyvinyl pyrrolidone powder in the mixed solvent was 0.025 g / mL or 0.05 g / mL, which was determined according to actual conditions.

[0072] 20 g of urea was loaded into a porcelain boat, which was placed in a muffle furnace, and the temperature was raised to 520 °C at a rate of 5 °C / min, and kept warm for 4 hours. After the muffle furnace was naturally cooled to room temperature, the obtained product was ground and collected to obtain g-C3N4 nanosheets (CN);

[0073] Weigh 0.5 g CN and 0.5 g TiO2 (P25) powder into a 50 mL grinding jar, then put in a stainless steel grinding ball, tighten the jar lid and place it in a freezer grinder. When the freezer grinder is cooled to -50 °C, adjust the freezer grinding parameters (grinding time 60 s, grinding frequency 30 Hz) to grind to obtain g-C3N4 / TiO2 powder (CG-CN / P25);

[0074] Weigh 0.1 g of CG-CN / P25 solid powder and place it in 15 mL of anhydrous ethanol solution, ultrasonicate for 2 h, and then magnetically stir for 1 h to make CG-CN / P25 evenly dispersed in the ethanol system to obtain a g-C3N4 / TiO2 electrospray solution;

[0075] The electrospinning machine is placed on one side of the drum collecting device, and the electrostatic sprayer is placed on the other side of the drum collecting device. Electrospinning and electrostatic spraying are performed simultaneously. The CA / PVP spinning solution is transferred to a syringe to prepare for electrospinning. When the electrospinning machine starts working, the CA / PVP nanofibers are collected by the drum collecting device, and a handheld electrosprayer filled with g-C3N4 electrospray solution is used to work at the same time, spraying for 6-8s at a certain interval until the spinning is completed, and the EE-CA / PVP / CGCN / P25 fiber membrane is obtained. Among them, the electrospinning process parameters are as follows: the spinning temperature and humidity are 25°C and 50%, respectively; the spinning positive and negative voltages are 10kV and -5kV, respectively; the feed rate is 0.4ul / min; the distance between the spinneret and the drum collecting device is 15cm.

[0076] The EE-CA / PVP / CGCN / P25 fiber membrane was immersed in deionized water for 24 h to remove the polyvinyl pyrrolidone and freeze-dried to obtain the rice straw-derived cellulose acetate / g-C3N4 / TiO2 fiber membrane, which was recorded as EE-CA / CGCN / P25. (0.10) Fiber membrane.

[0077] Example 2

[0078] The preparation process was basically the same as that in Example 1, where 0.05 g of g-C3N4 / TiO2 powder was mixed with 15 mL of C2H5OH to obtain a rice straw-derived cellulose acetate / g-C3N4 / TiO2 fiber membrane, denoted as EE-CA / CGCN / P25. (0.05) Fiber membrane.

[0079] Example 3

[0080] The preparation process was basically the same as that in Example 1, wherein 0.15 g of g-C3N4 / TiO2 powder was mixed with 15 mL of C2H5OH to obtain a rice straw-derived cellulose acetate / g-C3N4 / TiO2 fiber membrane, denoted as EE-CA / CGCN / P25. (0.15) Fiber membrane.

[0081] In order to further illustrate the key points of this patent, a comparative case is added for illustration.

[0082] Comparative Example 1

[0083] The CG-CN / P25 powder was prepared by the same method as in Example 1, and the CA / PVP spinning solution was prepared by the same method as in Example 1. 0.10 g of the CG-CN / P25 powder was weighed and placed in the CA / PVP spinning solution, and magnetic stirring was performed for 12 h to obtain the CA / PVP / CGCN / P25 spinning solution.

[0084] The uniformly stirred CA / PVP / CGCN / P25 spinning solution was electrospun, and the spinning parameters were as follows: spinning temperature 25°C, humidity 45%, spinning positive and negative voltages 16kV and -6kV respectively, liquid flow rate 1.5ul / min, and the distance between the needle and the collection device was 15cm;

[0085] Finally, E-CA / PVP / CGCN / P25 was prepared by the above electrospinning technology. (0.10) The fiber membrane was immersed in deionized water for 24 h to remove PVP and freeze-dried to obtain E-CA / CGCN (0.10) Fiber membrane.

[0086] Comparative Example 2

[0087] The same rice straw-derived acetate fiber (CA) as in Example 1 was prepared, and CA was directly electrospun to obtain a pure CA fiber membrane.

[0088] The photocatalytic performance of the fiber membranes prepared in Examples 1-3 and Comparative Examples 1-2 was analyzed and relevant photocatalytic tests were performed.

[0089] 1. Photocatalytic test

[0090] (1) Photocatalytic degradation test

[0091] The photocatalytic activity of EE-CA / CG-CN / P25 fiber membrane under visible light irradiation was evaluated using different organic dyes Rhodamine B (RhB), methylene blue (MB) and methyl orange (MO) as simulated organic pollutants, and all tests were repeated 3 times. First, 50 mg of membrane photocatalyst was added to 50 mL of organic dye aqueous solution (10 mg / L). The above photocatalyst suspension was stirred in the dark for 30 minutes under magnetic stirring. After reaching adsorption-desorption equilibrium, xenon lamp irradiation was used as simulated sunlight irradiation, and the circulating condensed water was set to 20 ° C. 5 mL of equal amount was sampled every 5 minutes, and the resulting solution was filtered through a 0.22 μm filter membrane. The concentrations of RhB, MB and MO solutions were measured at 554 nm, 664 nm and 465 nm respectively using a UV-visible spectrophotometer.

[0092] (2) Photocatalytic cycle test

[0093] In order to verify the stability of the EE-CA / CG-CN / P25 fiber membrane, the membrane catalyst was subjected to 5 cycles of testing under the same photocatalytic conditions as mentioned above: after the photocatalytic test, the EE-CA / CG-CN / P25 fiber membrane was collected and repeatedly washed with anhydrous ethanol and deionized water to make the catalyst surface colorless, and then dried and then subjected to cycle testing. This process was repeated 5 times.

[0094] (3) Photocatalytic antibacterial test

[0095] The photocatalytic antibacterial activity of EE-CA / CGCN / P25 fiber membrane against Escherichia coli was detected by plate colony counting method. All tests were carried out in parallel 3 times. The nutrient source of bacteria was LB (1g beef extract, 1g NaCl, 2g peptone, 4g agar powder, 200mL H2O). All glassware was sterilized at 121℃ for 30min before testing. The photocatalytic antibacterial test process is described as follows: First, 50mg of EE-CA / CGCN / P25 (0.10) The fiber membrane is placed in a beaker and diluted with 0.9% NaCl solution. Secondly, the bacteria are taken out of the culture solution and added to the beaker containing the sample so that the bacteria and the sample are fully mixed and in contact in a dark environment. Third, a xenon lamp (λ>420nm) is used as a light source for vertical downward irradiation, and constant stirring is maintained throughout the test. At fixed time intervals, 1mL of the mixture is transferred with a pipette and diluted to an appropriate concentration. Finally, 0.1ml of the bacterial solution is evenly applied to the culture medium using the plate coating method. It is then placed in a constant temperature incubator and cultured overnight at 37°C. The number of colonies on each plate is counted using a colony counter to calculate the photocatalytic inhibition rate of the sample.

[0096] 1. Related characterization and performance analysis

[0097] (1) Effect of CN / P25 cryo-grinding parameters

[0098] In order to investigate the effects of three freezing grinding parameters, namely grinding ball diameter, grinding time and grinding frequency, on the photocatalytic degradation of RhB by CN / P25, a single factor experiment was conducted with the photocatalytic degradation rate as an indicator, based on a fixed grinding ball diameter of 4 mm, grinding time of 210 s and grinding frequency of 30 Hz. First, the effect of grinding ball diameter on the photocatalytic ability of CN / P25 was explored. The results are shown in Figure 2. Figure 1 (a) When the grinding ball diameters are 2 mm, 4 mm and 8 mm respectively, the photocatalytic degradation rate of CN / P25 powder for 10 mg / L RhB solution increases first and then decreases with the increase of grinding ball diameter. It can be seen that under certain grinding time and frequency, grinding balls with a diameter of 4 mm are the best choice.

[0099] Depend on Figure 1 (b) It can be seen that: in the early stage of grinding, the photocatalytic degradation rate of CG-CN / P25 powder to 10 mg / L RhB solution increases with the increase of grinding time. When the grinding time exceeds 210 s, its photocatalytic degradation rate to 10 mg / L RhB solution decreases. Therefore, 210 s is selected as the optimal grinding time.

[0100] Grinding frequency is the oscillation frequency. The cryo grinder oscillates the grinding jar at a high frequency through vertical swinging, so that the potential energy of the grinding balls is converted into kinetic energy to hit the sample, and then converted into chemical energy to compound the CN powder and P25 powder. The higher the oscillation frequency, the more times the grinding jar completes up and down oscillations per minute, and the number of times the grinding balls hit the sample per unit time also increases. Figure 1 (c) It can be seen that when the grinding frequency increases from 10 Hz to 30 Hz, the photocatalytic degradation rate of CG-CN / P25 powder to 10 mg / L RhB solution is significantly improved. When the grinding frequency increases to 50 Hz, its degradation rate is greatly reduced. Therefore, the optimal grinding frequency is 30 Hz. In summary, the optimal conditions for cryo-grinding treatment are grinding time 210 s, grinding ball diameter 4 mm, and grinding frequency 30 Hz.

[0101] In addition, the mass ratio of g-C3N4 and TiO2 also has a certain effect on the degradation ability of CG-CN / P25. The mass ratios of g-C3N4 and TiO2 were selected as 1:1, 1:2, 1:3, 2:1 and 3:1, and the photocatalytic degradation effect of RhB was compared. The results are shown in Figure 4 .2d. It can be observed that when the mass ratio of g-C3N4 to TiO2 is 1:1, the degradation rate of RhB is the highest, reaching 99.99% under visible light irradiation for 8 min. Therefore, the use of CG-CN / P25 (1:1) The solid powder was used for subsequent analysis.

[0102] (2) Morphology and structure analysis

[0103] The surface morphology and microstructure of different samples are shown in Figure 2. Figure 2 As shown, the SEM image of CG-CN / P25 clearly shows that the g-C3N4 nanosheets are tightly combined with the TiO2 nanoparticles ( Figure 2 (ab)), the nanosheets are small and the TiO2 particles are evenly dispersed. This is conducive to exposing more active sites, thereby promoting charge transfer and improving photocatalytic degradation ability. Since powdered catalysts are not conducive to recycling, CA is used as a carrier to load CG-CN / P25 on nanofibers by electrospinning-electrospray method, which is convenient for recycling while maintaining its excellent photocatalytic degradation ability. When the CG-CN / P25 loading is 0.05g, a small amount of CG-CN / P25 particles are loaded on the fiber surface ( Figure 2 (cd)). When the loading amount increases to 0.10 g, it can be observed that the fiber surface is covered with CG-CN / P25 particles, which are small in size and evenly dispersed ( Figure 2 (ef)). After adding 0.15 g of CG-CN / P25 particles, it was found that the fiber structure surface became rougher and the CG-CN / P25 particles showed obvious agglomeration ( Figure 2 (gh)). Similarly, when the loading amount of CG-CN / P25 was 0.10 g, the preparation process was changed and E-CA / CGCN / P25 prepared by the traditional electrospinning method was (0.10) The CG-CN / P25 particles in the fiber membrane are no longer anchored on the fiber surface, but are completely wrapped inside the fiber, increasing the fiber diameter, and the CG-CN / P25 particles are obviously accumulated ( Figure 2 (ij)). From EE-CA / CGCN / P25 (0.10) TEM image of fiber membrane ( Figure 2 (kl)), it can be observed that CG-CN / P25 particles are tightly anchored on the fiber surface, which is consistent with the SEM results. Figure 2 (l) Obvious lattice fringes can be seen, and the interplanar spacing is 0.353 nm, corresponding to the (101) plane of TiO2, which indicates that g-C3N4, TiO2 and nanofibers are tightly combined together.

[0104] (3) X-ray diffraction (XRD) analysis

[0105] Figure 3 Describes CN / P25, CG-CN / P25, E-CA / CGCN / P25 (0.10) XRD spectra of EE-CA / CGCN / P25 fiber membranes with different CG-CN / P25 contents. The peaks at 2θ=25.3°, 38.0°, 48.1°, 54.2°, 55.0°, 62.3°, 69.2°, 70.1° and 75.2° are respectively attributed to the (101), (004), (200), (105), (211), (204), (116), (220) and (215) crystal planes of anatase TiO2. Both CN / P25 and CG-CN / P25 powders have typical TiO2 diffraction peaks and a characteristic diffraction peak at 27.6°, which is related to the (002) crystal plane of g-C3N4. In addition, there are no additional hybrid peaks except the characteristic diffraction peaks of g-C3N4 and TiO2, which indicates that the cryo-grinding process has no effect on the lattice structure and phase purity of TiO2 and g-C3N4. (0.10) The diffraction peaks of the fiber membranes are roughly the same, both containing characteristic diffraction peaks of TiO2 and g-C3N4, indicating that the obtained materials still maintain the rutile TiO2 and graphite-like phase g-C3N4 crystal structures, and there are no other impurities.

[0106] (4) Fourier transform infrared spectroscopy (FT-IR) analysis

[0107] To detect CN / P25, CG-CN / P25, E-CA / CGCN / P25 (0.10) The composition information and chemical bonds of EE-CA / CGCN / P25 fiber membranes with different CG-CN / P25 contents were analyzed by Fourier transform infrared spectroscopy. Figure 4 For CN / P25 and CG-CN / P25 powders, four main absorption regions can be clearly observed ( Figure 4 (a) 3000-3500cm -1 The broad band at 1200-1600 cm is attributed to the OH stretching vibration of water molecules adsorbed on the surface of TiO2 and g-C3N4 and the NH stretching vibration of g-C3N4. -1 The strong bands in the region and 1241, 1319, 1403, 1465 and 1573cm -1 The characteristic peak at 810 cm is attributed to the typical stretching vibration of the CN heterocycle, while the peak at 810 cm -1 The peak at 400–700 cm-1 corresponds to the bending vibration of the triazine unit. -1 The main peaks are attributed to the Ti-O and Ti-O-Ti stretching vibrations in anatase TiO2 crystals.

[0108] like Figure 4 As shown in (b), all the main absorption peaks of TiO2 and g-C3N4 appear in E-CA / CGCN / P25 (0.10) and the EE-CA / CGCN / P25 fiber membranes with different CG-CN / P25 contents. However, compared with the Ti-O-Ti stretching vibration absorption band of pure CG-CN / P25 powder, a slight shift of this Ti-O-Ti vibration mode was observed in the prepared composites, which is due to the interfacial interaction between TiO2 and g-C3N4 layers. This strong interfacial interaction between TiO2 and g-C3N4 layers will promote electron transfer, thereby improving the photocatalytic efficiency. In addition, the 1047, 1236, 1375 and 1752 cm -1 The characteristic peaks at correspond to the stretching vibration of the COC pyran ring of CA, the stretching vibration of CO, CH and C=O of the acetoxy group. It can be seen that we have successfully loaded CG-CN / P25 onto CA nanofibers and prepared a series of CA / CGCN / P25 fiber membranes.

[0109] (5) X-ray energy spectrum (EDS) and element distribution map (Mapping)

[0110] Figure 5These are the EDS spectra and Mapping images of the CG-CN / P25 solid powder, which were used to study the chemical composition, elemental content, and distribution of the CG-CN / P25 solid powder. It can be seen from Figure 5 (a) that there are four elements, namely C, N, O, and Ti, in CG-CN / P25. The mass percentages of the elements are 22.88%, 35.05%, 28.92%, and 13.15% respectively, and the atomic percentages are 29.35%, 38.56%, 27.85%, and 4.23% in sequence. These elements come from g-C3N4 and TiO2. This indicates that the CG-CN / P25 solid powder has been successfully prepared through cryogenic milling treatment. From Figure 5 (b-f), it can be clearly observed that the four elements C, N, O, and Ti are evenly distributed, which is consistent with the above EDS results.

[0111] Figure 6 These are the EDS spectra and Mapping images of the EE-CA / CN / P25 (0.10) fiber membrane. Similarly, there are also four elements, namely C, N, O, and Ti, in the EE-CA / CN / P25 (0.10) fiber membrane. The mass percentages and atomic percentages of the elements are shown in the table in Figure 6 (a). As shown in Figure 6 (b-f), the elemental mapping results confirm the presence of C, N, O, and Ti elements, and also indicate that CG-CN / P25 is evenly dispersed in the EE-CA / CN / P25 (0.10) fiber membrane. This further demonstrates that the EE-CA / CN / P25 (0.10) fiber membrane has been successfully constructed, and CG-CN / P25 is tightly combined with CA.

[0112] (6) Specific surface area and pore size distribution characterization

[0113] Figure 7 Table 1 compares the specific surface areas and pore structure characteristics of CG / CN, CG-CN / P25, EE-CA / CN / P25 (0.10) and E-CA / CN / P25 (0.10) fiber membranes. Obviously, all samples exhibit typical type-IV isotherms and H3 hysteresis loops at relatively high pressures (0.8 < P / P0 < 1.0), indicating the presence of mesoporous structures

[181] . Compared with the CN / P25 solid powder with a specific surface area of 30.00 m 2 g -1 , the specific surface area of CG-CN / P25 obtained by cryogenic milling of CN / P25 increases to 45.58 m 2 g -1In addition, the pore volume of CG-CN / P25 solid powder increased from 14.52 cm 3 g -1 Increased to 15.27cm 3 g -1 Therefore, cryo-grinding treatment helps to increase the specific surface area and pore volume of the catalyst. By comparing the specific surface area and pore structure differences of CA / CGCN / P25 fiber membranes prepared by different methods, it can be found that EE-CA / CN / P25 prepared by electrospinning-electrospray (0.10) The specific surface area of ​​the fiber membrane (11.72m 2 g -1 ) and pore volume (20.82 cm 3 g -1 ) are higher than E-CA / CN / P25 prepared by electrospinning (0.10) Fiber membrane (8.31m 2 g -1 and 16.14cm 3 g -1 ). This shows that compared with the traditional electrospinning method, the specific surface area and pore volume of the composite material prepared by electrospinning-electrospinning method are improved.

[0114] Table 1 Specific surface area and pore structure parameters of materials

[0115]

[0116]

[0117] (7) UV-Visible absorption spectroscopy (DRS) characterization

[0118] The ultraviolet-visible diffuse reflectance spectroscopy (UV-Vis) was used to measure the (0.10) The light absorption characteristics of EE-CA / CGCN / P25 fiber membranes with different CG-CN / P25 contents are shown in Figure 2. Figure 8 As shown. It can be observed that, compared with E-CA / CGCN / P25 (0.10) Compared with the EE-CA / CGCN / P2 fiber membranes, the EE-CA / CGCN / P2 fiber membranes with different CG-CN / P25 contents showed almost the same absorption band edge, and the absorption intensity in the entire visible light band was improved. In addition, with the increase of CG-CN / P25 loading, the absorption intensity in the visible light region also gradually increased. (0.10) and E-CA / CGCN / P25 (0.10) The band gap energy values ​​of the two can be calculated by the following formula:

[0119] (αhv)n =A(hv-Eg)

[0120] Wherein: α, h, ν, Eg and A represent the absorption coefficient, Planck constant, optical frequency, band gap energy value and proportional constant respectively, and n is 2.

[0121] like Figure 8 As shown in (b), (αhν) 2 The relationship between EE-CA / CGCN / P25 and photon energy hν can be estimated (0.10) and E-CA / CGCN / P25 (0.10) The band gap energy values ​​of EE-CA / CGCN / P25 are 2.54eV and 4.42eV respectively. (0.10) The band gap is much smaller than that of E-CA / CGCN / P25 (0.10) The band gap of 2.5 nm indicates that its light absorption rate is higher.

[0122] (8) Three-dimensional fluorescence (3DEEM) characterization

[0123] Fig. 9 CN / P25, CG-CN / P25, E-CA / CGCN / P25 (0.10) Fluorescence spectrophotometer (PL) spectra of EE-CA / CGCN / P25 fiber membranes with different CG-CN / P25 contents. As can be seen from the figure, compared with CN / P25, the fluorescence intensity of CG-CN / P25 solid powder treated with cryo-grinding is reduced, which indicates that the free carrier recombination rate is reduced. (0.10) The EE-CA / CGCN / P25 fiber membranes with different CG-CN / P25 contents all have strong emission peaks near 450nm, and the fluorescence curves of each sample are roughly the same. With the increase of CG-CN / P25 loading, the fluorescence intensity of the fiber membrane increases first and then decreases, indicating that when 0.10g of CG-CN / P25 solid powder is added, CG-CN / P25 can be evenly distributed on the nanofibers. When CG-CN / P25 is 0.15g, EE-CA / CGCN / P25 (0.15) The fluorescence intensity of the fiber membrane increased, indicating that the free carrier recombination rate increased, which may be due to the agglomeration of CG-CN / P25. (0.10) E-CA / CGCN / P25 prepared by electrospinning (0.10) Fiber membrane, comparison found that EE-CA / CGCN / P25 (0.10) The fluorescence signal intensity of the fiber membrane is much lower than that of E-CA / CGCN / P25 (0.10)fiber membrane, which indicates that the electrospinning-electrospray method anchors CG-CN / P25 on the fiber surface, allowing the photogenerated electrons and photogenerated holes to separate rapidly, greatly reducing the recombination of photogenerated-electron-hole pairs and improving the separation efficiency of photogenerated carriers, thereby allowing more photogenerated carriers to effectively participate in the photocatalytic degradation reaction.

[0124] 3. Other performance analysis

[0125] (1) Photoelectrochemical performance test

[0126] Fig.10 Depicts EE-CA / CGCN / P25 (0.10) and E-CA / CGCN / P25 (0.10) Photocurrent curve and electrochemical impedance diagram of fiber membrane under visible light irradiation. Fig.10 As can be seen in (a), EE-CA / CGCN / P25 (0.10) and E-CA / CGCN / P25 (0.10) The fiber membranes all have obvious photocurrent changes, and EE-CA / CGCN / P25 (0.10) The photocurrent intensity is greater than that of E-CA / CGCN / P25 (0.10) Fiber membrane. This shows that the preparation of CA / CGCN / P25 fiber membrane by electrospinning-electrospray can effectively improve the separation efficiency of photogenerated electron-hole pairs. The radius of the arc in the EIS spectrum represents the charge transfer resistance on the surface of the electrode material. EIS results are shown in Fig.10 (b) EE-CA / CGCN / P25 (0.10) The charge transfer resistance is greater than that of E-CA / CGCN / P25 (0.10) fiber membrane. It can be seen that EE-CA / CGCN / P25 (0.10) The results show that the electron transfer efficiency is more efficient. At the same time, it is further proved that compared with the traditional electrospinning method, the electrospinning-electrospray method helps to improve the interfacial charge transfer efficiency and carrier transport efficiency, thereby improving the photocatalytic degradation performance of the catalyst.

[0127] (2) Optical contact angle test

[0128] Fig.11 CA, EE-CA / CGCN / P25 (0.10) and E-CA / CGCN / P25 (0.10) The test results of the contact angle of the fiber membrane to water. As can be seen from the figure, the contact angle of the CA membrane is 83°, and the contact angle of EE-CA / CGCN / P25 is 83°. (0.10) The contact angle of the fiber membrane is 23°, E-CA / CGCN / P25 (0.10) The contact angle of the fiber membrane is 50°, which shows that compared with the pure CA membrane, the EE-CA / CGCN / P25(0.10) and E-CA / CGCN / P25 (0.10) The hydrophilicity of the fiber membrane has been improved. In addition, EE-CA / CGCN / P25 (0.10) The hydrophilicity of the fiber membrane is the highest, much higher than that of pure CA membrane and E-CA / CGCN / P25 prepared by electrospinning. (0.10) Fiber membrane. Proof EE-CA / CGCN / P25 (0.10) The fiber membrane is super hydrophilic.

[0129] (3) Photocatalytic performance

[0130] MB and TC were used as pollutant models to evaluate the performance of E-CA / CGCN / P25 under visible light irradiation. (0.10) The photocatalytic performance of EE-CA / CGCN / P25 fiber membranes with different CG-CN / P25 contents is shown in Figure 2. Fig.12 (ad) shown. The amount of CG-CN / P25 catalyst added is very important for the photocatalytic activity of the EE-CA / CGCN / P25 nanocomposite. Therefore, it is necessary to preliminarily determine the optimal loading amount of CG-CN / P25 through testing in order to obtain relatively good photocatalytic activity. Under visible light irradiation, with the increase of the amount of CG-CN / P25 added, the degradation of MB by the EE-CA / CGCN / P25 fiber membrane first increased and then decreased, which means that the optimal addition amount of CG-CN / P25 is 0.10g. Comparing the CA / CGCN / P25 nanocomposites prepared by two different methods, it can be found that at 30 minutes of illumination, the EE-CA / CGCN / P25 prepared by electrospinning-electrospray method (0.10) The degradation rate and rate constant of the fiber membrane were 99.75% and 0.1411min respectively. -1 , which are higher than E-CA / CGCN / P25 prepared by electrospinning (0.10) Fiber membrane (96.45% and 0.0812min -1 In addition, when TC was used as a simulated pollutant and irradiated under visible light for 30 min, EE-CA / CGCN / P25 (0.10) The fiber membrane still showed the best degradation rate, which was consistent with the above-mentioned photocatalytic degradation results of MB. (0.10) The rate constant of the fiber membrane reached 0.0781min -1 , respectively EE-CA / CGCN / P25 (0.05) EE-CA / CGCN (0.15) 、E-CA / CGCN / P25 (0.10)The photocatalytic activity of CA / CGCN / P25 fiber membrane was 1.56, 1.15 and 1.52 times that of the fiber membrane. This further indicates that the combination of appropriate amount of CG-CN / P25 loading and electrospinning-electrospray method can effectively improve the photocatalytic activity of CA / CGCN / P25 fiber membrane.

[0131] Due to EE-CA / CGCN / P25 (0.10) The fiber membrane showed the best photocatalytic degradation performance for both MB and TC, so EE-CA / CGCN / P25 was selected (0.10) The fiber membrane photocatalytically degrades other types of dyes, and studies its adsorption and oxidation activity in photocatalytic degradation of different types of dyes. The results are as follows Fig.12 (ef) Comparison of the three dyes, when irradiated with visible light for 30 min, EE-CA / CGCN / P25 (0.10) The degradation rates of RhB, MB and MO by the fiber membrane were 76.42%, 99.75% and 50.65%, respectively, and the rate constants were 0.0231 min -1 、0.1411min -1 、0.0232min -1 Therefore, EE-CA / CGCN / P25 (0.10) The fiber membrane has photocatalytic degradation effect on three dyes: RhB, MB and MO. The photocatalytic degradation effect on MB is the strongest, followed by RhB and MO. (0.10) The fiber membrane has excellent photocatalytic degradation and water treatment properties.

[0132] In addition, using EE-CA / CGCN / P25 (0.10) The fiber membrane was subjected to repeated photocatalytic degradation tests on MB dye solution (such as Fig.13 After five cycles of repeated degradation, EE-CA / CGCN / P25 (0.10) The degradation rate of MB by the fiber membrane decreased by only about 6%. This result was due to the adsorption and deposition of organic degradation byproducts during the photocatalytic process. These deposited substances could be (0.10) A strong surface complex is formed on the fiber membrane surface, blocking EE-CA / CGCN / P25 (0.10) Active sites of fiber membranes. In EE-CA / CGCN / P25 (0.10) After repeated use for 5 times, the degradation rate can still reach more than 90%. (0.10) The fiber membrane maintains relatively stable photocatalytic activity and good reusability.

[0133] (4) Three-dimensional fluorescence spectroscopy

[0134] Fig.14 Demonstrated 3D fluorescence detection of EE-CA / CGCN / P25 (0.10) Photocatalytic degradation of different organic dyes by fiber membranes. Fig.14 As shown in (a), the fluorescence signal of the original solution of MB dye is strong, and the two three-dimensional fingerprint peaks at 650-750 / 250-350nm and 650-750 / 550-700nm are the fluorescence characteristic peaks of MB. After the dark reaction reaches adsorption equilibrium for 30 minutes, the intensity of the two three-dimensional fingerprint peaks weakens (as shown in Figure 2). Fig.14 (b) shows that EE-CA / CGCN / P25 (0.10) The fiber membrane has a certain adsorption and degradation effect on MB. As the photocatalytic reaction proceeds for 30 min (e.g. Fig.14 (c) shows that the fluorescence signal is significantly reduced, indicating that MB is basically degraded. In addition, when RhB and MO are used as simulated pollutants, the fluorescence characteristic peaks of RhB are at 550-575 / 620-660nm and 225-275 / 575-650nm (as shown in Figure 2). Fig.14 (d)), 300-400 / 250-350nm is the 3D fingerprint characteristic peak of MO (as shown in Fig.14 (g) shows that the intensity of the 3D fingerprint peak does not change before and after the dark reaction (as shown in Fig.14 (e)(h)), indicating that the membrane has almost no adsorption effect on RhB and MO. After irradiation with visible light for 30 min, the spectral signals of RhB and MO also changed accordingly, but they were not completely degraded (as shown in Figure 2). Fig.14 (f)(i)). Therefore, for the three organic dyes, EE-CA / CGCN / P25 (0.10) The fiber membrane has the best selectivity for MB and has different degrees of degradation effects on RhB and MO.

[0135] (5) Photocatalytic mechanism

[0136] like Fig.15 As shown, the free radical quenching test was used to determine the EE-CA / CGCN / P25 (0.10) The active free radical species of fiber membrane. Generally speaking, benzoquinone (BQ), triethanolamine (TEOA) and isopropyl alcohol (IPA) capture superoxide radicals (·O2 - ), photogenerated holes (h + ) and hydroxyl radicals (·OH). After adding IPA, EE-CA / CGCN / P25 (0.10)The photocatalytic degradation ability of the fiber membrane for MB dye decreased slightly, from 98.77% in the blank test to 70.68%. After adding BQ and TEOA, the photocatalytic ability decreased significantly, and the degradation rates dropped to 28.05% and 51.88%, respectively. This result shows that O2 - 、h + Both ·O2 and ·OH radicals participated in the photocatalytic degradation of MB. - is the main free radical. In the MB photodegradation process, EE-CA / CGCN / P25 (0.10) The inhibitory effect of free radical generation of fiber membrane: O2 - >h + >·OH.

[0137] (6) Photocatalytic antibacterial

[0138] EE-CA / CGCN / P25 was evaluated by plate count method (0.10) Antibacterial properties of fiber membranes against Escherichia coli. Fig.16 The growth of E. coli in the presence and absence of photocatalyst and when the catalyst was shielded from light is shown. Here, the bacteria remaining without photocatalyst and with photocatalyst but shielded from light are used as the control group, and it can be seen that the growth of E. coli is good, indicating that the antibacterial activity is minimal. However, in EE-CA / CGCN / P25 (0.10) In the presence of fiber membrane, after irradiation with visible light (λ>420nm) for 40 minutes, the residual bacteria were significantly reduced, and after 60 minutes, there were few bacteria left. EE-CA / CGCN / P25 (0.10) The fiber membrane showed strong antibacterial activity. Fig.16 (mn) It can be seen that EE-CA / CGCN / P25 (0.10) The antibacterial efficiency of the fiber membrane reached 98% after 40 minutes of illumination and nearly 100% after 60 minutes.

[0139] In summary:

[0140] The cryogenic grinding technique was used to tightly combine CN and TiO2 (P25) to prepare the CG-CN / P25 catalyst, which was loaded onto nanofibers by electrospinning-electrospray technology to prepare the EE-CA / CGCN / P25 fiber membrane. Compared with the traditional electrospinning method, the g-C3N4 / TiO2 particles of the EE-CA / CGCN / P25 fiber membrane were more exposed on the surface of the nanofibers, providing more active sites, which is beneficial to improve the photocatalytic performance. At the same time, the EE-CA / CGCN / P25 fiber membrane exhibited a lower band gap, a larger specific surface area and stronger superhydrophilicity.

[0141] The EE-CA / CGCN / P25 fiber membrane was used for the photocatalytic degradation of RhB. The results showed that the catalyst could achieve a 99% degradation rate of RhB when the light was irradiated for 8 min. When the loading amount of CG-CN / P25 was 0.10 g, the EE-CA / CGCN / P25 (0.10) The fiber membrane exhibited the best photocatalytic activity, with a degradation rate of up to 99.80% for MB and 92.10% for TC in 30 min, and showed good stability and reusability after 5 cycles.

[0142] Evaluation of EE-CA / CGCN / P25 by photocatalytic antibacterial test (0.10) The antibacterial properties of the fiber membrane. The test results show that when EE-CA / CGCN / P25 is irradiated under visible light (λ>420nm) for 60min, (0.10) The antibacterial rate against Escherichia coli reached 99.90%. (0.10) Fiber membrane catalysts have broad application prospects in the fields of degradation of water pollutants and antibacterial properties.

[0143] The above are only preferred embodiments of the present invention and the technical principles used. Those skilled in the art will understand that the present invention is not limited to the specific embodiments described herein, and that various obvious changes, readjustments and substitutions can be made by those skilled in the art without departing from the scope of protection of the present invention. Therefore, although the present invention is described in more detail through the above embodiments, the present invention is not limited to the above embodiments, and may include more other equivalent embodiments without departing from the concept of the present invention, and the scope of the present invention is determined by the scope of the appended claims.

Claims

1. A method for preparing a rice straw-derived cellulose acetate / g-C3N4 / TiO2 fiber membrane, characterized in that: The following steps are involved: Mixing dichloromethane and acetic acid uniformly to obtain a mixed solvent, adding rice straw-derived cellulose acetate and polyvinyl pyrrolidone powder into the mixed solvent and stirring to obtain a CA / PVP spinning solution; The urea is heated in a muffle furnace to prepare g-C3N4 nanosheets, the g-C3N4 nanosheets and TiO2 powder are weighed and put into a cryogenic grinding machine, and the cryogenic grinding parameters are adjusted to grind to obtain g-C3N4 / TiO2 powder; The g-C3N4 / TiO2 powder is placed in an anhydrous ethanol solution, subjected to ultrasonic treatment, and subjected to magnetic stirring to obtain a g-C3N4 / TiO2 powder electrospray solution; EE-CA / PVP / g-C3N4 / TiO2 fiber membrane was prepared by electrospinning-electrospray technology, CA / PVP spinning solution and g-C3N4 / TiO2 powder electrospray solution were used for electrospinning and electrospinning respectively, g-C3N4 / TiO2 powder was evenly anchored on the fiber surface, and EE-CA / PVP / g-C3N4 / TiO2 fiber membrane was obtained; The EE-CA / PVP / g-C3N4 / TiO2 fiber membrane was immersed in deionized water to remove polyvinyl pyrrolidone, and then freeze-dried to obtain a rice straw-derived cellulose acetate / g-C3N4 / TiO2 fiber membrane.

2. The method for preparing the rice straw-derived cellulose acetate / g-C3N4 / TiO2 fiber membrane according to claim 1, characterized in that: The mass ratio of the rice straw-derived cellulose acetate to the polyvinyl pyrrolidone powder is (3-5):1; the volume ratio of the dichloromethane to the acetic acid is (1-3):1, and the concentration of the polyvinyl pyrrolidone powder in the mixed solvent is 0.025-0.05 g / mL.

3. The method for preparing the rice straw-derived cellulose acetate / g-C3N4 / TiO2 fiber membrane according to claim 2, characterized in that: The concentration of the g-C3N4 / TiO2 powder relative to the mixed solvent is 0.01 to 0.025 g / mL; in the g-C3N4 / TiO2 powder electrospray solution, the concentration of the g-C3N4 / TiO2 powder relative to the anhydrous ethanol is 0.003 to 0.01 g / mL.

4. The method for preparing the rice straw-derived cellulose acetate / g-C3N4 / TiO2 fiber membrane according to claim 1, characterized in that: When the heating reaction is carried out in the muffle furnace, the temperature is raised to 500-550°C at a rate of 3-6°C / min and kept warm for 4-6 hours; when the g-C3N4 nanosheets and the TiO2 powder are ground, the mass ratio is 1:1; the freezing grinding parameters include: the grinding time is 30-90s, and the grinding frequency is 25-35Hz.

5. The method for preparing the rice straw-derived cellulose acetate / g-C3N4 / TiO2 fiber membrane according to claim 1, characterized in that: The electrospinning-electrospraying technology device comprises an electrospinning machine, an electrostatic sprayer and a rotary drum collecting device, wherein the electrospinning machine is placed on one side of the rotary drum collecting device, and the electrostatic sprayer is placed on the other side of the rotary drum collecting device; When the electrospinning-electrospraying technology is used, an electrospinning machine and an electrostatic sprayer are used simultaneously to perform electrospinning and electrostatic spraying respectively, and a rotary drum collection device is used for collection. The electrostatic sprayer is not connected to a high-voltage power supply when in use. The electrospinning-electrospraying technology allows the nanoparticles in the electrospray liquid to be evenly dispersed on the fiber surface.

6. The method for preparing the rice straw-derived cellulose acetate / g-C3N4 / TiO2 fiber membrane according to claim 5, characterized in that: The electrospinning process parameters include: spinning temperature of 23-27°C, humidity of 45-55%, spinning positive voltage of 8-12kV, spinning negative voltage of -4--6kV, feeding speed of 0.3-0.5ul / min, and the distance between the spinneret and the drum collecting device of 10-20cm.

7. The method for preparing the rice straw-derived cellulose acetate / g-C3N4 / TiO2 fiber membrane according to claim 1, characterized in that: The preparation method of the rice straw-derived cellulose acetate comprises: The rice straw is washed, dried, crushed and sieved to obtain rice straw powder, the rice straw powder is pretreated with an ethanol solution in a high temperature reactor, and then subjected to an alkali treatment and H2O2 bleaching to obtain rice straw-derived cellulose; Acetic anhydride and glacial acetic acid are added to the rice straw-derived cellulose to prepare rice straw-derived cellulose acetate through acetylation reaction.

8. The method for preparing the rice straw-derived cellulose acetate / g-C3N4 / TiO2 fiber membrane according to claim 7, characterized in that: The rice straw particle size is 50 to 100 meshes; During the pretreatment process, the mass concentration of the ethanol solution is 60-70wt%, the heating reaction temperature is 160-240°C, and the reaction time is 2-3h; During the alkali treatment and H2O2 bleaching process, 4-6 wt% alkali solution is used to stir and react at 85-95°C for 1.5-2.5 hours, and after the reaction is completed, it is filtered, and then heated and stirred with 2 wt% H2O2 solution at 65-75°C for 1.5-2.5 hours to obtain rice straw-derived cellulose; During the acetylation reaction, the mass ratio of the rice straw-derived cellulose to the acetic anhydride is 1:(3-5), and the concentration range of the rice straw-derived cellulose in the glacial acetic acid is 0.05-0.07 g / mL.

9. A rice straw derived cellulose acetate / g-C3N4 / TiO2 fiber membrane, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8.

10. A use of the rice straw derived cellulose acetate / g-C3N4 / TiO2 fiber membrane according to claim 9, characterized in that: The rice straw-derived cellulose acetate / g-C3N4 / TiO2 fiber membrane is used as a photocatalyst in water pollution treatment and photocatalytic sterilization.

Citation Information

Patent Citations

  • Chitosan / graphite phase carbon nitride / titanium dioxide nanofiber membrane as well as preparation method and application thereof

    CN111250056A

  • Degradable spinning raw material, degradable fiber membrane and degradable protective cover

    CN111286175A

  • Method for preparing cellulose acetate and P25 porous flexible fiber membrane through electrospinning, obtained porous flexible fiber membrane and application of porous flexible fiber membrane

    CN112430910A

  • Composite membrane as well as preparation method and application thereof

    CN114405284A

  • Degradable composite material for injection molding and preparation method thereof

    CN116875015A